Artificially low salaries and tax dodging - LIU, Hern Kuan (Institutional Knowledge at Singapore Management University, 2020)
In the recent case of Wee Teng Yau v Comptroller of Income Tax, the Singapore Supreme Court considered the issue of tax avoidance by professionals for the first time. The case involved a dentist, Dr Wee, who was initially employed by Alfred Cheng Orthodontic Clinic Pte Ltd (ACOC). Subsequently, he incorporated Straighten Pte Ltd (SPL), of which he was the sole director and shareholder. Dr Wee continued to provide the same dental services to ACOC's patients as he had done before. However, instead of paying Dr Wee directly for his services, ACOC paid for his services to SPL, which in turn paid Dr Wee a salary and a director's fee.